An Effectiveness of the LAOPDR Instructional Method in Chemistry Teaching and Learning Management at Chomphet Secondary School, Luang Prabang Province - BOUNYALUCK, Khampheun; VATHANAVONG, Thongthiane; SOULIYA, Toulakhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
A study of teaching and learning management using the LAOPDR teaching method in chemistry at Chomphet Secondary School, Luang Prabang Province, this study aimed to (1) examine the effectiveness of chemistry instructional activities based on the 70/70 criterion, and (2) investigate the learning achievement of Grade 11 students at Chomphet Secondary School during the 2025–2026 academic year through the implementation of the LAOPDR teaching approach. The sample consisted of 30 students from Class 5/1, selected through a convenience sampling method. Research instruments included five lesson plans, five formative assessments comprising five items each, and a 25-item pre-test and post-test. Data were analyzed using basic statistics mean and standard deviation as well as the efficiency indices E1/E2 and the effectiveness index (E.I). Calculations were performed using SPSS Version 22. The findings revealed that: 1) The efficiency of the chemistry instructional activities using the LAOPDR approach reached 82.80/77.60, which exceeded the predetermined 70/70 criterion. 2) The effectiveness of student learning achievement was 0.6440, indicating an improvement of 64.40% following the intervention.